2019
DOI: 10.1002/slct.201901978
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of D‐π‐A Molecular with Functional Imidazole Group: Achieving High Color Contrast Mechanochromic Behavior and Selectively Detection of Picric Acid in Aqueous Medium

Abstract: Multi‐stimuli responsive D‐π‐A molecular (named CZIZ) comprising of carbazole as D, dicyano as A and imidazole as functional group was designed and synthesized. The photophysical properties showed that CZIZ possessed the property of aggregation‐induced emission enhancement (AIEE) property, which was verified by UV‐vis absorption and fluorescence spectra. In addition, the large twisted structure and loose arrangement induced CZIZ performed high color contrast mechanochromic (MC) behaviors from 537 nm to 584 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…45 Previous studies have shown that the introduction of imidazole as a functional group in molecules could achieve specific recognition of picric acid (PA) over various nitroaromatic compounds (NACs) by exhibiting a characteristic change in spectroscopy and/or luminescent color owing to the protonbinding nature of imidazole. [46][47][48] Since PA is considered a hazard that is widely used in powerful explosives, plasticizers, and pharmaceuticals, 49,50 the development of PA sensors in recent years has attracted considerable attention. A fluorescence titration assay was carried out to assess the sensing performance.…”
Section: Resultsmentioning
confidence: 99%
“…45 Previous studies have shown that the introduction of imidazole as a functional group in molecules could achieve specific recognition of picric acid (PA) over various nitroaromatic compounds (NACs) by exhibiting a characteristic change in spectroscopy and/or luminescent color owing to the protonbinding nature of imidazole. [46][47][48] Since PA is considered a hazard that is widely used in powerful explosives, plasticizers, and pharmaceuticals, 49,50 the development of PA sensors in recent years has attracted considerable attention. A fluorescence titration assay was carried out to assess the sensing performance.…”
Section: Resultsmentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins anion and imidazolium moiety and π-π interactions between pyrene ring and picrate anion were observed. Probe 72 82 (chart 8) in DMF gave emission maxima at 460 nm which in 90% water was red-shifted to 574 nm due to formation of spherical aggregates with 233 nm diameter. These aggregates showed 96% fluorescence quenching with 10 equivalents of picric acid and LOD as 3.5 μM picric acid.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In particular, donor-p-acceptor (D-p-A) dyad molecules are widely used molecular systems because of the easy tailoring of the photophysical property by changing the sub-units such as donor, acceptor, and p-linker. Thus, an adequate combination of sub-units in the D-p-A dyad system is the key to achieving the desired electrochemical and photophysical properties for a wide range of applications, such as organic light-emitting diodes (OLEDs), [10][11][12][13][14][15][16][17] dye-sensitized solar cells (DSSCs), [18][19][20][21] organic photovoltaics (OPVs), [22][23][24] photoelectrochemical cells (PECs), [25][26][27][28] uorescence sensors, [29][30][31] mechanochromic materials, [32][33][34] nonlinear optical materials, 35,36 and nanostructured materials. [37][38][39] The notable features of D-p-A dyads are intramolecular charge transfer (ICT) and photoinduced electron transfer (PET) in the ground and excited states because of the large electronic dipoles.…”
Section: Introductionmentioning
confidence: 99%
“… 1–9 In particular, donor–π–acceptor (D–π–A) dyad molecules are widely used molecular systems because of the easy tailoring of the photophysical property by changing the sub-units such as donor, acceptor, and π-linker. Thus, an adequate combination of sub-units in the D–π–A dyad system is the key to achieving the desired electrochemical and photophysical properties for a wide range of applications, such as organic light-emitting diodes (OLEDs), 10–17 dye-sensitized solar cells (DSSCs), 18–21 organic photovoltaics (OPVs), 22–24 photoelectrochemical cells (PECs), 25–28 fluorescence sensors, 29–31 mechanochromic materials, 32–34 nonlinear optical materials, 35,36 and nanostructured materials. 37–39 …”
Section: Introductionmentioning
confidence: 99%